Provenance, diagenesis, and paleoclimate of Albian-Lower Turonian deposits in the Douala sub-basin, Cameroon: Sedimentological, mineralogical, and petrographical approaches - Christel Sobdjou-Kemteu; Milan Stafford Tchouatcha; Wael Fathi Galal; Soureiyatou Fadil-Djenabou; Usman Abubakar; Francis Thierry Togozo; Emmanuel Ndjeng (Solid Earth Sciences)
The sedimentological, mineralogical, and petrographic compositions of the Albian - Lower Turonian deposits at four sites in the northern part of the Douala sub-basin located in the heart of the Guinea Gulf were investigated to determine their provenance, paleoclimate, and diagenetic effects from thirty-eight (38) samples. Several lithologies are identified, ranging from clays/shales to silty clays, poor consolidated fine-to coarse-grained sandstones, and conglomerates to conglomeratic sandstones. The deposits are made up of successive positive sequences in the eastern part of the Mungo River and cyclic deposits in the western part. The sandstones are primarily arkose wacke, secondarily arkose, subarkose, sublith-arenite, and rare lithic arenite and wacke derived from the Neoproterozoic basement formed during the Pan-African orogenesis. The presence of heavy minerals such as tourmaline, kyanite and sillimanite indicates that the deposits originate from plutonic and metamorphic sources. The rarity of these latest in the sediments suggest the intense chemical weathering that has affected the source rocks. These deposits are mainly proximal. Additionally, the association of polycrystalline quartz with undulatory extinction and monocrystalline quartz with non-undulatory extinction suggests a mixed source. The various microstructures and morphologies of zircon grains including prismatic, sub-angular and sub-prismatic shapes further support a mixed provenance. The dominance of prismatic shape and non-undulatory monocrystalline quartz grains indicates a predominance of plutonic sources. X-ray diffraction analysis revealed that kaolinite is the dominant clay mineral found in clayey facies, though its moderate to low quantity indicates a more humid climate during the Albian-Cenomanian and a less humid climate during the Cenomanian. Physical alteration processes have mainly affected the studied deposits.